An Intervention Framework to Facilitate Psychological Trauma Management in High-Risk Occupations - Jonker, Bouwer E.; Graupner, Lene Ilyna; Rossouw, Lizelle (Frontiers in Psychology, 2020)
Various psychological trauma management programs (PTMPs) are offered to assist employees who have been exposed to a traumatic event in the workplace. There is, however, limited literature available on how employees in high-risk occupations experience these programs. This study qualitatively explored the experiences of PTMPs from the perspective of employees working in three high-risk occupations. The purpose of this study was to explore the experiences of the participants in order to compile a framework that could help support and improve the productivity and wellbeing of employees affected by work-related trauma. The study used a qualitative research design based on an approach informed by interpretivism and social constructivism. A multiple-case study was used as research strategy to incorporate three sectors in South Africa, namely mining, policing, and emergency medical services. Data were gathered through semi-structured interviews and focus groups, and analyzed using thematic analysis. The findings across the three sectors showed effective strategies considered by participants to manage psychological trauma. These strategies include multiple counseling sessions, face-to-face counseling, regaining control, and receiving support. Strategies that were viewed as ineffective include inability of counselors to relate to the participants’ work environments, lack of involvement, lack of supervisor support, unavailability of counseling and specialized skills, premature resuming of duties, and a single-dimension approach. Based on the findings, an intervention framework is proposed to address psychological trauma in high-risk occupations.